Review of the genus Eotilla Schuster, 1949 (Hymenoptera: Typhoctinae, Eotillini) 2: species from Chile - Brothers, Denis J.; Torréns, Javier (Zootaxa, 2024)
The Eotillini primarily occur in Argentina, Bolivia and Chile. This paper treats the Chilean species of Eotilla Schuster, 1949. In addition to E. mickeli Schuster, 1949, six new species are described, based on males: E. ferruginea Brothers & Torréns sp. nov., E. punctata Brothers & Torréns sp. nov., E. setosa Brothers & Torréns sp. nov., E. fidalgoi Brothers & Torréns sp. nov., E. packeri Brothers & Torréns sp. nov. and E. pallidipes Brothers & Torréns sp. nov.. The previously unknown female of E. mickeli is also described. The distributions of both genera of Eotillini and their possible evolutionary history and zoogeography as related to the uplift of the Andes Mountains are briefly discussed.